Serbia and Montenegro - Republic of Serbia : Accounting and Auditing - World Bank (Washington, DC, 2012)
This Report provides an assessment of accounting and auditing standards and practices in Serbia. It uses International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) as benchmarks, and draws on good practices in the field of accounting and audit regulation to assess the quality of financial information and make policy recommendations. It highlights significant weaknesses in the quality of financial information, which are detrimental to sustainable economic growth and may allow systemic risks to perpetuate. Further, it highlights significant shortcomings in the legal and regulatory framework and stresses that addressing those should be a priority for Serbia in order to create a robust legal foundation for the provision of reliable financial information to market participants. Moreover, this Report demonstrates that legal requirements and competence alone are not enough - the commitment to deploy such competence is also essential. Market forces provide certain positive incentives to comply with high standards, but experience in Serbia (and developed economies) suggests that countervailing disincentives operate to discourage such compliance. More emphasis should be placed on the deterrent incentives of robust monitoring and enforcement regimes to achieve a full and balanced combination of capacity and incentives. The recommendations of this Report are mutually supportive in some obvious ways and require a holistic, multi-disciplinary approach to implementation. Also, the Report only sketches the policy recommendations to enhance the quality of corporate financial reporting. The Report strongly recommends that Serbia establishes a multidisciplinary National Steering Committee (NSC) for accounting and auditing reform to advise policymakers, regulators, and other stakeholders regarding the implementation of the recommendations. Finally, the Report recommends that the members of the NSC should include senior representatives of stakeholder institutions with adequate support staff to follow through on the substantial reform agenda ahead.